226k views
2 votes
Enter a recursive rule for the geometric sequence.

2,−6,18,−54,...

2 Answers

6 votes

Answer:

see explanation

Explanation:

A recursive rule allows us to obtain any term in the sequence from the previous term.

These are the terms of a geometric sequence with common ratio r

r = - 6 ÷ 2 = 18 ÷ - 6 = - 54 ÷ 18 = - 3

Thus to obtain a term in the sequence multiply the previous term by - 3


a_(n+1) = - 3
a_(n) with a₁ = 2

User Shannell
by
5.3k points
5 votes

Answer:


a_n=-3a_(n-1) where
a_1=2

Explanation:

Recursive means you want to define a sequence in terms of other terms of your sequence.

The common ratio is what term divided by previous term equals.

The common ratio here is -6/2=18/-6=-54/18=-3.

Or in terms of the nth and previous term we could say:


(a_n)/(a_(n-1))=r

where r is -3


(a_n)/(a_(n-1))=-3

Multiply both sides by the a_(n-1).


a_n=-3a_(n-1) where
a_1=2

User Ggdx
by
5.5k points